Function of the conserved FHIPEP domain of the flagellar type III export apparatus, protein FlhA. Issue 2 (10th February 2016) - Barker, Clive S.; Inoue, Tomoharu; Meshcheryakova, Irina V.; Kitanobo, Seiya; Samatey, Fadel A.
Summary: The Type III flagellar protein export apparatus of bacteria consists of five or six membrane proteins, notably FlhA, which controls the export of other proteins and is homologous to the large family of FHIPEP export proteins. FHIPEP proteins contain a highly‐conserved cytoplasmic domain. We mutagenized the cloned Salmonella flhA gene for the 692 amino acid FlhA, changing a single, conserved amino acid in the 68‐amino acid FHIPEP region. Fifty‐two mutations at 30 positions mostly led to loss of motility and total disappearance of microscopically visible flagella, also Western blot protein/protein hybridization showed no detectable export of hook protein and flagellin. There were two exceptions: a D199A mutant strain, which produced short‐stubby flagella; and a V151L mutant strain, which did not produce flagella and excreted mainly un‐polymerized hook protein. The V151L mutant strain also exported a reduced amount of hook‐cap protein FlgD, but when grown with exogenous FlgD it produced polyhooks and polyhook‐filaments. A suppressor mutant in the cytoplasmic domain of the export apparatus membrane protein FlhB rescued export of hook‐length control protein FliK and facilitated growth of full‐length flagella. These results suggested that the FHIPEP region is part of the gate regulating substrate entry into the export apparatus pore. Abstract : FlhA plays an important role in controlling the substrate specificity of the flagellar export system, and this study was undertaken to investigate the contribution of the FHIPEP‐containing domain of FlhA. The results showed that the FHIPEP domain is critical for coordinating protein export with hook assembly to control the hook length at about 55 nm. It is the first time that the FlhA FHIPEP domain has been shown to be directly involved in subunit sorting.